RELEVANSI DEEP LEARNING DENGAN HIDDEN CURRICULUM DALAM PEMBENTUKAN KARAKTER PADA MATA PELAJARAN PAI - Giantomi Muhammad; Desfita Irmayanti; Iwan Sanusi (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
The deep learning approach is currently a focus of national education policy because it emphasizes active student involvement, deepening understanding of the material, and the ability to relate learning to everyday life. This approach includes elements of meaningful learning, mindful learning, and joyful learning. In line with this, the hidden curriculum exists as an unwritten curriculum that implicitly shapes student norms, values, attitudes, and behavior through school culture. Deep learning and the hidden curriculum play an important role in character formation, particularly in Islamic Religious Education (PAI) subjects that emphasize the internalization and practice of Islamic values. This study aims to examine the relevance of deep learning and the hidden curriculum in character formation in PAI learning. The method used is a literature review with a qualitative approach, analyzed through thematic synthesis. The results show that the collaboration of deep learning and the hidden curriculum can strengthen the formation of character and noble morals of students in PAI learning.